In vitro evaluation of the cytotoxic potential of Ficus palmata and its combination with chemotherapy and photodynamic therapy. (1st May 2023) - Aziz, Bushra; Khurshid, Ahmat; Ahmat, Lubna; Khan, Junaid Ahmad; Alam, Masroor; Ikram, Masroor
Abstract: Ficus palmata (F. palmata) is a medicinally very rich plant that is used as a folk medicine to treat many diseases. This study investigated the anticancer effect of 70% ethanolic leaves extract of F. palmata alone and its combinational study with photosense-mediated photodynamic therapy (PDT) and doxorubicin hydrochloride (Dox-HCl) on rhabdomyosarcoma (RD) cells. The inhibitory dose (IC50 ) was calculated from dose response analysis of 24 h post exposure of F. palmata (400, 200, 100, 50, 25, 12.5 µ g ml −1 ), Dox-HCl (4, 3, 2, 1 µ M), and photosense (80, 40, 20, 10, 5 µ M, 10 J cm −2 ) mediated PDT. These IC50 doses were further used to assess the anticancer effect of F. palmata in combination with photosense-mediated PDT and Dox-HCl. The in vitro findings showed that the 70% ethanolic F. palmata leaves extract has anticancer potential, and has the ability to enhance the anticancer effect in combination with other therapies. Moreover, the neoadjuvent combination of F. palmata with PDT and chemotherapy has a synergistic effect. This study provides evidence that F. palmate leaves extract possesses promising anticancer activity, and more research is needed to isolate the specific bioactive compound for cancer treatment.